ACTUAL PROBLEMS OF ACCOUNTING ORGANIZATION ON THE FINANCIAL RESPONSIBILITY CENTERS - G. A. Adamova (Вестник университета)
The successful functioning of large companies is directly related to the quality of information support for management. One of the important places in the management accounting system is the allocation of responsibility centers and the construction of the financial structure of the company. The article considers key questions of the organization of accounting on the financial responsibility centers and the main problems, facing economic services in the formation of management accounting. The possible relationships between the organizational and financial structures have been disclosed. The recommendations on the distribution of responsibilities and fixing of indicators for structural units in order to implement the established plan of activities have been given. The detail problem of the established indicators, as well as the possibilities of managerial influence from linear managers has been considered.